Image Navigation for FY-4A Lightning Mapping Imager - Jing Wang (IEEE, 2021)
Navigation of images from lightning mapping instruments in geostationary orbits is very important for data applications. However, few scientific peer-reviewed papers have been reported, except a few works in the prelaunch tests. On December 11, 2016, China launched the three-axis stabilized geostationary meteorological satellite Fengyun-4A (FY-4A), which carries a lightning mapping imager (LMI) onboard. LMI is now providing lightning observations above the equator at 104.7˚E and covers a large portion of the eastern Asian continent. In this article, a new method has been set up to perform the image navigation for FY-4A/LMI. First, landmarks were used to calculate thermal deformation parameters and edge-binding technique was proposed to solve the inconsistency between the two tubes’ pointing directions. Second, temperatures of the mounting plate were used to be correlated with the daytime thermal deformation parameters to deduce the nighttime pointing directions when the landmarks were not available. Furthermore, the operational timetable for LMI was determined by analyzing the variations of navigation accuracy caused by the landmark observation interval and the sensor's integration time for landmarks. Analysis of about 9200 background images of 153 consecutive days from the housekeeping data were investigated to validate the proposed methods’ accuracy for LMI image navigation. Compared to the baseline algorithm, navigation accuracy has been improved on average from 2–10 pixels to 1 pixel. The FY-4A/LMI navigation system has been put into operation since May 1, 2018, which has been in normal service ever since.